Performance comparison of RF energy harvesting rectifiers designed in CMOS FDSOI 28 nm with dynamic back gate biasing and BiCMOS 55 nm technology. Issue 5 (22nd January 2021) - Awad, Mohamad; Benech, Philippe; Duchamp, Jean‐Marc
Abstract: A comparison between two Dickson voltage multipliers realized in two technologies, fully depleted silicon on insulator (FDSOI) 28 nm and Bipolar CMOS (BiCMOS) 55 nm is presented. The assessment is based on the I–V characteristics measurements of transistors configured as diodes; and on the measurements of one and two stages of Dickson multipliers designed for RF energy harvesting. The I–V characteristics show that FDSOI technology is profitable owing to its smaller threshold voltage ( V th ), and a leakage current less than that of BiCMOS. Consequently, for the same input voltage, the output voltage acquired in FDSOI is greater than that achieved with BiCMOS. Moreover, for rectifiers designed in FDSOI, a dynamic back gate bias could be employed to enhance the performance by adjusting dynamically the V th and the leakage current.